The Effect of Work Motivation and Leadership Styles on Employee Performance (Case Study at the Class III Port Administration Unit Office - Serui, Yapen Regency, Papua) - Rifai Karim (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze work motivation and leadership style on employee performance. This research is a quantitative study using the method of causality analysis. The sample of this study was 53 employees of the Class III Serui Port Administration Unit (KUPP). The research instrument was a questionnaire with a 5-point Likert scale. Data were analyzed by multiple linear regression test. The results of this study indicate that 1) work motivation has a significant effect on employee performance at the Class III Serui Papua Port Administration Unit Office. The higher the work motivation possessed by employees, the higher the resulting performance. 2) Leadership style has a significant effect on the performance of employees at the Serui Papua Class III Port Administration Unit Office.